Dispersion of graphene in chlorosulfonated polyethylene by slurry compounding. (7th July 2018) - Yang, Zhijun; Xu, Zongchao; Zhang, Liqun; Guo, Baochun
Abstract: It remains a huge challenge to realize the homogeneous graphene dispersion in elastomer matrix by a simple and general compounding method. Herein, we develop a straightforward slurry compounding method for preparation of rubber/graphene composites with well-dispersed graphene. Specifically, TPG (tea polyphenol reduced graphene)/ethanol slurry was first collected by solvent exchange after the reduction of graphene oxide by tea polyphenol and then directly melt compounded with chlorosulfonated polyethylene (CSM) in a two-roll mill to produce the composites. As revealed by the XRD and morphological studies, TPG homogeneously dispersed in CSM matrix, which together with the strong interfacial interaction between TPG and CSM contribute to the remarkable improvement in mechanical properties of the resulted composites. We envision that the present work offers a straightforward yet effective methodology for preparing high-performance elastomer/graphene composites via conventional melt compounding.